Alkylation‐, Heating‐, and Doping‐Induced Emission Enhancement of a Polyaromatic Tube in the Solid State. Issue 5 (8th February 2018) - Kuroda, Kiyonori; Otsuki, Masafumi; Yazaki, Kohei; Sei, Yoshihisa; Akita, Munetaka; Yoshizawa, Michito
Abstract: A polyaromatic tube with a subnanometer‐sized cavity was efficiently prepared on a gram‐scale through the stereo‐controlled cyclotrimerization of a diphenylanthracene derivative as a key step. The facile exterior alkylation of the polyaromatic framework leads to a moderately fluorescent tube (R=‐OC10 H21 ; Φ F =20 %) in the solid state. The emission intensity of the solid‐state alkyl‐substituted tube is remarkably enhanced upon heating (up to 1.6 times, Φ F =31 %) as well as doping with fluorescent dyes (up to 4.2 times, Φ F =83 %) through efficient energy transfer. Abstract : Taking the tube : A polyaromatic tube was efficiently prepared on a gram‐scale through a stereo‐controlled homocoupling reaction as a key step. The facile exterior alkylation leads to a moderately fluorescent tube in the solid state. The emission quantum yield of the solid‐state alkyl‐substituted tube is remarkably enhanced upon heating (up to 1.6 times) as well as doping with fluorescent dyes (up to 4.2 times).